Color‐nutrient associations: Implications for product design of dietary supplements. Issue 5 (29th July 2022) - Motoki, Kosuke; Yamada, Asumi; Spence, Charles
Abstract: Dietary supplements are prevalent and represent a huge (and still growing) global market. Such products are intended to enhance health and wellness as well as to supplement diets. Compared to the large amount of dietary supplements research on nutrition, dietetics, and medicine, far less research has been conducted in the realm of sensory and consumer science. Product design is undoubtedly an important element of any brand's success, no matter what the category, and can be used to convey various symbolic meanings to the consumer. Drawing on research on color psychology and product design, the present research aimed to clarify the associations (or expectations) that consumers have with the particular product design of dietary supplements. Across four studies, two of which were preregistered, participants were asked to choose a color that they felt best matched each of the named nutrients. The results consistently demonstrate that people associate nutrients with particular colors (i.e., color patches; Study 1) and to capsule/container color; Studies 2–4. Vitamins supplements in general, as well as vitamins C and D, in particular, were frequently matched with the colors yellow and orange. Dietary fiber supplement was often matched with green. Although mineral supplements were frequently matched with blue, each kind of mineral appeared to have its own unique association with specific colors (magnesium/iron with gray, calcium with white). Protein supplements (protein, amino acid) are frequently matched with the colors orange and red. Taken together, these findings demonstrate how people associate nutrients with specific visual design features and thus contribute practical knowledge concerning the design of dietary supplements. Practical Applications: Our findings provide practical implications for effective communication strategies for nutrition with the consumer. Color is an important design element, and the design of nutritional supplements and their packaging is no exception in this regard. Designers and marketers can use our findings to help create better visual designs for dietary supplements and their packaging to help meet consumers' expectations. Moreover, our findings might also be fruitfully applied to marketing communications for functional foods (e.g., vitamin‐enriched foods, mineral‐enriched foods). Marketers may be able to capitalize on our findings concerning color‐nutrition associations in order to effectively promote functional foods.